DIFFICULTIES OF DEAF STUDENTS IN SOLVING WORD PROBLEMS - Fa'ani, Arini Mayan; Sari, Melati Indah; Santoso, Sandy Tegariyani Putri (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The purpose of this study was to find out what difficulties were experienced by deaf students in solving word problems of integer arithmetic operations. This research used   qualitative approach with a descriptive type of research. Data collection techniques used are tests and interviews that has been collected from 6 students of 7th grade in SMPLB YPTB Malang. The results of this study are; (1) Subjects with difficulty using the concept are caused because students have difficulty in remembering some conditions and expressed in mathematics terms that represent it; (2) Subjects with difficulty using the principle are caused because of they are not careful in carrying out calculations and difficult to state a principle, also cannot apply the principle; (3) The subject has difficulty solving verbal problems are caused of the subject only has a little understood vocabulary. This will have an impact on the subject's inability to use the data in the word problems, interpret the language or terms contained in it and the difficulty in drawing conclusions.